Investigation of Adjoint of Linear Transformation and Some Its Important Properties - Yousefi, Najibullah; Popalzai, Laila; Jalal, Hadia (Journal for Research in Applied Sciences and Biotechnology, 2022)
Linear operator on inner product space is including adjoint operator, self adjoint operator, unitary operator, normal operator ,… (self adjoint operator and unitary operator is normal operator but convers is not true at all) in this paper I discussed about adjoint operator and self adjoint operator of linear transformation and some important properties. In this paper first I defined the linear transformation, inner product space, adjoint linear transformation, self adjoint operator and very important relevant properties and theorem.